Haemophilia Joint Health Score in healthy adults playing sports. (24th October 2013) - Sluiter, D.; Foppen, W.; de Kleijn, P.; Fischer, K.
Summary: To evaluate outcome of prophylactic clotting factor replacement in children with haemophilia, the Haemophilia Joint Health Score (HJHS) was developed aiming at scoring early joint changes in children aged 4–18. The HJHS has been used for adults on long‐term prophylaxis but interpretation of small changes remains difficult. Some changes in these patients may be due to sports‐related injuries. Evaluation of HJHS score in healthy adults playing sports could improve the interpretation of this score in haemophilic patients. The aim of this study was to evaluate the HJHS scores in a cohort of young, healthy men participating in sports. Concomitant with a project collecting MRI images of ankles and knees in normal young adults, HJHS scores were assessed in 30 healthy men aged 18–26, participating in sports one to three times per week. One physiotherapist assessed their clinical function using the HJHS 2.1. History of joint injuries was documented. MRI images were scored by a single radiologist, using the International Prophylaxis Study Group additive MRI score. Median age of the study group was 24.3 years (range 19.0–26.4) and median frequency of sports activities was three times per week (range 1–4). Six joints (five knees, one ankle) had a history of sports‐related injury. The median overall HJHS score was 0 out of 124 (range 0–3), with 60% of subjects showing no abnormalities on HJHS. All joints were normal on MRI. These results suggest that frequent sports participation and related injuries are not related with abnormalities in HJHS scores.